1986
DOI: 10.1126/science.231.4744.1414
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Venus Winds by Ground-Based Radio Tracking of the VEGA Balloons

Abstract: A global array of 20 radio observatories was used to measure the three-dimensional position and velocity of the two meteorological balloons that were injected into the equatorial region of the Venus atmosphere near Venus midnight by the VEGA spacecraft on 11 and 15 June 1985. Initial analysis of only radial velocities indicates that each balloon was blown westward about 11,500 kilometers (8,000 kilometers on the night side) by zonal winds with a mean speed of about 70 meters per second. Excursions of the data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…This global trend was derived by Ignatiev et al (2009) from VIRTIS-M spectroscopy and VMC images and was later confirmed by Lee et al (2012) by joint analysis of the VeRa and VIRTIS instruments on Venus Express. A recent detailed work based on VIRTIS data confirms this trend (Haus et al, 2014) which is also in agreement with earlier radiative transfer results (Zasova et al, 2007) and in situ measurements during the descent of the Venera and Pioneer Venus probes (Schubert, 1983) and from tracking of VEGA balloons (Preston et al, 1986).…”
Section: Cloud Altitudes and Vertical Wind Shearssupporting
confidence: 81%
“…This global trend was derived by Ignatiev et al (2009) from VIRTIS-M spectroscopy and VMC images and was later confirmed by Lee et al (2012) by joint analysis of the VeRa and VIRTIS instruments on Venus Express. A recent detailed work based on VIRTIS data confirms this trend (Haus et al, 2014) which is also in agreement with earlier radiative transfer results (Zasova et al, 2007) and in situ measurements during the descent of the Venera and Pioneer Venus probes (Schubert, 1983) and from tracking of VEGA balloons (Preston et al, 1986).…”
Section: Cloud Altitudes and Vertical Wind Shearssupporting
confidence: 81%
“…VLBI tracking of planetary spacecraft for navigation was developed in the mid‐1970s and has been frequently used since then [ Thornton and Border , 2003]. VLBI observations of planetary probes have also been used to measure lunar rotational dynamics [ King et al , 1976; Slade et al , 1977] and winds on Venus [ Counselman et al , 1979; Preston et al , 1986; Sagdeyev et al , 1992]. We note that the VLBI technique offers extremely high angular resolution that is inversely proportional to the baseline (distance) between the telescopes involved.…”
Section: Overview Of the Ground‐based Observationsmentioning
confidence: 99%
“…The Venus ground atmospheric conditions (9e +6 Pa and 700 K) do not allow any long‐duration deployment on the surface, even modern technology cannot withstand these temperatures and pressures for more than a couple of hours. In contrast, balloons with infrasound sensors would overpass these limitations and may be able to probe the interior structure of a planet by acoustic pulses from seismic activity on its surface (Garcia et al, ) and its atmosphere structure and dynamics (Preston et al, ).…”
Section: Introductionmentioning
confidence: 99%